Value of routine intraoperative frozen sections of proximal bile duct margins in perihilar cholangiocarcinoma, a retrospective multicenter and matched case-control study. Issue 12 (December 2022) - Nooijen, L.E.; Franken, L.C.; de Boer, M.T.; Buttner, S.; van Dieren, S.; Koerkamp, B. Groot; Hoogwater, F.J.H.; Kazemier, G.; Klümpen, H.J.; Kuipers, H.; Olthof, P.B.; Swijnenburg, R.J.; et al.
Abstract: Background: Currently, the potential benefits of additional resection after positive proximal intraoperative frozen sections (IFS) in perihilar cholangiocarcinoma (pCCA) on residual disease and oncological outcome remain uncertain. Therefore, the aim of this study is to investigate the number of R0 resections after additional resection of a positive proximal IFS and the influence of additional resections on overall survival (OS) in patients with pCCA. Materials and methods: A retrospective, multicenter, matched case-control study was performed, including patients undergoing resection for pCCA between 2000 and 2019 at three tertiary centers. Primary outcome was the number of achieved 'additional' R0 resections. Secondary outcomes were OS, recurrence, severe morbidity and mortality. Results: Forty-four out of 328 patients undergoing resection for pCCA had a positive proximal IFS. An additional resection was performed in 35 out of 44 (79.5%) patients, which was negative in 24 (68.6%) patients. Nevertheless, seven out of these 24 patients were eventually classified as R1 resection due to other positive resection margins. Therefore, 17 (48.6%) patients could be classified as "true" R0 resection after additional resection. Ninety-day mortality after R1 resections was high (25%) and strongly influenced OS. After correction for 90-day mortality, median OS after negative additional resection was 33 months (95%CI:29.5–36.5) compared to 30 months (95%CI:24.4–35.6) after initial R1 ( P = 0.875) and 46 months (95%CI:32.7–59.3) after initial R0 ( P = 0.348). Conclusion: There were only 17 patients (out of a total of 328 patients) that potentially benefitted from routine IFS. Additional resection for a positive IFS leading to R0 resection was not associated with improved long-term survival.